Strategy-proofness of the probabilistic serial rule on sequentially dichotomous domains - LIU, Peng (Institutional Knowledge at Singapore Management University, 2017)
A class of preference domains is proposed: sequentially dichotomous domains. On any sequentially dichotomous domain, the probabilistic serial rule (Bogomolnaia and Moulin (2001)) is sd-strategy-proof. In addition, any sequentially dichotomous domain is maximal for the probabilistic serial rule to be sd-strategy-proof.